2021
DOI: 10.1073/pnas.2111215118
|View full text |Cite
|
Sign up to set email alerts
|

Sediment load determines the shape of rivers

Abstract: Understanding how rivers adjust to the sediment load they carry is critical to predicting the evolution of landscapes. Presently, however, no physically based model reliably captures the dependence of basic river properties, such as its shape or slope, on the discharge of sediment, even in the simple case of laboratory rivers. Here, we show how the balance between fluid stress and gravity acting on the sediment grains, along with cross-stream diffusion of sediment, determines the shape and sediment flux profil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 32 publications
(53 reference statements)
2
28
0
Order By: Relevance
“…As posited by Popović et al (2021) on the grounds of experiments on bedload‐dominated laboratory rivers (Abramian et al, 2020), an increase in sediment discharge progressively widens a river. The results of physical models of coarse‐bedded channels indicated that the reach‐averaged active channel width is positively correlated with the bedload transport rate (Peirce et al, 2018), clearing the way for the supposition that the active width and its variations can be adopted as parameters for estimating changes in coarse sediment fluxes.…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…As posited by Popović et al (2021) on the grounds of experiments on bedload‐dominated laboratory rivers (Abramian et al, 2020), an increase in sediment discharge progressively widens a river. The results of physical models of coarse‐bedded channels indicated that the reach‐averaged active channel width is positively correlated with the bedload transport rate (Peirce et al, 2018), clearing the way for the supposition that the active width and its variations can be adopted as parameters for estimating changes in coarse sediment fluxes.…”
Section: Methodsmentioning
confidence: 89%
“…Currently, pinpointing a direct association between the width of a river's active channel and the absolute values of sediment fluxes occurring at a given reach (e.g., expressed bed material load volume) is infeasible because this relationship is influenced by numerous river features (e.g., sediment grain size, transport capacity, morphological configuration) (e.g., Mueller & Pitlick, 2013, 2014). That said, Popović et al (2021) recently hypothesized that the shape of a river can be used as a proxy for sediment discharge. Peirce et al (2018) also demonstrated in a flume experiment that variations in the active channel width are positively correlated with changes in coarse sediment transport.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large part of the studies on erosion has considered the erosion of grains subjected to a unidirectional and homogeneous (translation invariant) tangential flow [14][15][16]. This configuration is relevant for dune formation in the desert [17][18][19][20][21], or for sediment transport in rivers [22][23][24][25]. Although this simple flow configuration allows obtaining relevant scaling laws for sediment erosion and transport, various configurations involve a granular bed subjected to a flow that is not homogeneous.…”
Section: Introductionmentioning
confidence: 99%